Factors Affecting Personal Tax Compliance With Sanctions as Moderating Variables (Empirical Study at Primary KPP North Bekasi) - Sri Mulyati; Hadri Mulya (Garuda Prestasi Nusantara Consulting, 2021)
This research was conducted to examine the factors that influence individual taxpayer compliance with sanctions as a moderating variable. This research was conducted at the Primary Tax Office in North Bekasi. Data collection techniques were carried out by distributing questionnaires as many as 170 respondents, but 5 respondents did not return the questionnaire and 165 respondents to the data conducted for the study. The data in this study are primary data and the method used in this research is quantitative method, using SPSS (Statistical Package for the Social Sciences version 22). The results of this study indicate that knowledge, tax awareness and tax environment have a positive effect on taxpayer compliance while sanctions as a moderating variable, it has no positive effect on taxpayer compliance.